MENGGALI NILAI-NILAI KEPAHLAWANAN MO’AN TEKA IKU DITINJAU DARI ASPEK PEMBELAJARAN PKn - Gustav Gisela Nuwa (Universitas Sriwijaya, 2020)
This study aims to determine the heroic values of Mo'an Teka Iku to find out the efforts to maintain the heroic values of Mo'an Teka Iku. This research is descriptive qualitative in order to obtain a picture of the heroic values of Mo'an Teka Iku according to figures society, cultural and elders by using related questions so that all data collected in accordance with the research objectives achieved. The results showed that the heroism values of Mo'an Teka Iku are as follows: Democracy, Responsibility, Nationalism, Willing to sacrifice, Fighting spirit, Openness, Courage and Patriotism and efforts to maintain the values of the heroism of Mo'an Teka Iku are education and participation.